2005
DOI: 10.1037/0090-5550.50.4.366
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient-Centered Information on Patients' Treatment Satisfaction and Outcomes in Traumatic Brain Injury Rehabilitation.

Abstract: To evaluate the effects on patients with traumatic brain injury (TBI) of detailed, personalized information about their injuries, acute care treatment, and rehabilitation progress. Participants: Twentyeight former or present military personnel (mean age ϭ 30 years) with moderate to severe TBI (mean of 29 days spent in intensive care before admission to TBI unit). Design: Two (personalized information vs. general information) ϫ 2 (high-vs. low-patient preference for health care information) factorial design. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 37 publications
(55 reference statements)
0
41
0
Order By: Relevance
“…Findings from Paul et al 12 suggest that both patients and their relatives would value even more attention to the tailoring of information to individual circumstances. Additional evidence from studies with other critical care populations, 19,21,22 leads us to surmise that information based on individual assessment of need and capability is likely to be more effective than the provision of generic information. Evidence from our review and other literature suggests that providing information can aid shared decision making during critical illness recovery and that, even in more unwell persons, participation strategies are feasible when the right support is provided.…”
Section: Meeting Individual Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from Paul et al 12 suggest that both patients and their relatives would value even more attention to the tailoring of information to individual circumstances. Additional evidence from studies with other critical care populations, 19,21,22 leads us to surmise that information based on individual assessment of need and capability is likely to be more effective than the provision of generic information. Evidence from our review and other literature suggests that providing information can aid shared decision making during critical illness recovery and that, even in more unwell persons, participation strategies are feasible when the right support is provided.…”
Section: Meeting Individual Needsmentioning
confidence: 99%
“…Publications from both critical care and other areas of practice [20][21][22][23][24][25] suggest that personalization of information, active involvement of patients and family members in identifying and meeting their own needs, and offering opportunities for reflection could all be important factors that can increase the effectiveness of critical care discharge information. Such views are supported by Knowles,26 who argues that adults are a diverse population with a range of experience and that adults learn best when goals and objectives are considered realistic and important to them and when they are actively involved.…”
mentioning
confidence: 99%
“…These ranged from providing clients with tailored information about their condition (Pegg et al, 2005) through to interventions targeting broader meta-cognitive processes, equipping clients with the skills to plan, execute and evaluate their own rehabilitation (Skidmore et al, 2011) or enabling client involvement in a collaborative process of identifying, working towards and evaluating rehabilitation goals Lane-Brown & Tate, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pegg et al (2005) found that providing personalised information on their injury and rehabilitation progress increased clients' exerted effort in subsequent physical but not speech therapy, and their improvement in cognitive rehabilitation.…”
Section: Information Provisionmentioning
confidence: 96%
See 1 more Smart Citation